ПОЛИМОРФИЗМ ГЕНА ЭНДОТЕЛИАЛЬНОЙ СИНТАЗЫ ОКСИДА АЗОТА И САХАРНЫЙ ДИАБЕТ 2 ТИПА (литературный обзор) - Ю. А. Сорокина; Л. В. Ловцова (SINAPS LLC, 2014)
This review is devoted to a problem of interpretations of scientific data in the field of genes polymorphism researches, especially endothelial nitric oxide synthase. It is difficult to evaluate gene associations with variety of clinically significant conditions. To define associations is essential in patients with diabetes mellitus because of its cardiovascular complications. The data about associations gives us abilities to develop new targets and tactics, providing personal approach to a disease management.